ANALISIS PARTISIPASI POLITIK PEREMPUAN DI ORGANISASI PARTAI HANURA KOTA GORONTALO DALAM PEMILIHAN ANGGOTA LEGISLATIF 2014 - Andi Yusuf Katili (International Interdisciplinary Conference on Sustainable Development Goals, 2018)
This study aims to analyze the Political Participation of Women in the Hanura Party Organization of Gorontalo City in the Election of 2014 Legislative Members. The method of research is descriptive with a qualitative approach. While techniques for collecting data used in this study are observation, interview and documentation, and technique of analyzing data used interactive model analysis. Based on the results of the research, it can be concluded that: (1) the political participation of women in the Hanura Party organization of Gorontalo City in the election of 2014 legislative members, is still considered low; (2) The low political participation of women can be seen from the results of legislative members elections, which only get one seat from five candidates submitted; (3) And out of twenty three cadres of women from the Hanura Party who have the right to be elected, only five people have advanced in the nomination or 19% of the total number of cadres who have not fulfilled the 30% quota; (4) The low political participation of women can also be seen from their involvement as functionaries of Hanura party administrators, especially at the branch level, only ranging from 19% to 28%; and (5) The low political participation of women as members or cadres can also be seen from their involvement in providing support in the form of contributions of energy, thought and material. Based on the conclusions above, it is suggested to the Hanura Party of Gorontalo City to increase the political participation of women in carrying out various coaching as follows: (1) It is necessary to increase the participation of women through intensive coaching with more attention to social, economic and political conditions; (2) It is necessary to increase participation through intensive socialization of the Law which provides more room for women in politics; (3) Regional regulations need to be formulated which enable active involvement of women in all fields and sectors; (4) it is necessary to motivate women by providing equal opportunities for men in various sectors; and (5) Political learning is needed for women so that they can understand the growing political conditions